2013
DOI: 10.1002/jsfa.6384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the moisture content of forced hot air on the postharvest quality and bioactive compounds of mango fruit (Mangifera indica L. cv. Manila)

Abstract: The moisture content of the heating air differentially modulated the postharvest ripening of 'Manila' mangoes. Moist air temporarily slowed down the ripening process of this mango cultivar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…According to Pérez‐Carrillo and Yahia (), β‐carotene and lycopene contents of papaya fruits are unaffected by hot water treatment; pulp color is maintained reflecting the stabilization of the carotenoid content. Ornelas‐Paz and Yahia () also reported that β‐carotene content in mango fruit treated with hot moist air was lower than in untreated fruit; this treatment inhibited the transcription of enzymes involved in carotenoid biosynthesis. Contrary to our results, Barman, Asrey, Pal, Jha, and Sharma () reported that mango fruit treated with calcium increased its carotenoid content.…”
Section: Resultsmentioning
confidence: 95%
“…According to Pérez‐Carrillo and Yahia (), β‐carotene and lycopene contents of papaya fruits are unaffected by hot water treatment; pulp color is maintained reflecting the stabilization of the carotenoid content. Ornelas‐Paz and Yahia () also reported that β‐carotene content in mango fruit treated with hot moist air was lower than in untreated fruit; this treatment inhibited the transcription of enzymes involved in carotenoid biosynthesis. Contrary to our results, Barman, Asrey, Pal, Jha, and Sharma () reported that mango fruit treated with calcium increased its carotenoid content.…”
Section: Resultsmentioning
confidence: 95%
“…[14][15][16] However, it can also give rise to changes in appearance and nutrient composition. Certain bioactive components, 17) and pharmacological activities such as antioxidant activity, 18) have been shown to increase in medicinal herbs after steaming.…”
Section: )mentioning
confidence: 99%
“…11,12 Among these methods, heat treatment with forms of hot air or hot water, is widely used for preventing postharvest decay and chilling injury. 13 It has been demonstrated that heat treatment could effectively delay softening in many fruits, such as tomato, 14 apple, 15 mango, 16,17 strawberry, 18,19 and Chinese bayberry. 20 Fruit softening is primarily due to the solubilisation and depolymerisation of cell wall components and structure.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, heat treatment with forms of hot air or hot water, is widely used for preventing postharvest decay and chilling injury . It has been demonstrated that heat treatment could effectively delay softening in many fruits, such as tomato, apple, mango, strawberry, and Chinese bayberry …”
Section: Introductionmentioning
confidence: 99%